Dynamic Characteristics of Inorganic Elements in Astragalus membranaceus at Different Growth Stages - Xia ZHAO; Jingjing SI; Kunpeng ZHAO; Shijun SHAO; Fude YANG; Jinliang FENG (Shipin gongye ke-ji, 2022)
Objective: To explore the dynamic accumulation characteristics of 10 inorganic elements including Mg, Ca, V, Mn, Fe, Co, Ni, Cu, Zn and Ba in Astragalus membranaceus at different growth stages, and determine the optimal harvesting period. Methods: Collected Astragalus membranaceus form different growth stages and determined its element contents by inductively coupled plasma mass spectrometry(ICP-MS), then analyzed its changes and accumulation rule by one-way ANOVA, principal component analysis(PCA), orthogonal projections to latent structures discriminant analysis(OPLS-DA) and correlation analysis. Results: The contents of 10 elements of Astragalus membranaceus at different growth stages were significantly different. The contents of Mg, Ca, V, Mn, Fe, Ni, Cu and Co reached the peak in October, and Ba reached the peak in June. The contents of above element were the lowest in August. The content of Zn in September was significantly higher and in July was significantly lower than that in other growing seasons (P<0.05). The contents of 10 elements all showed a dynamic trend of decreasing first and then increasing. Correlation analysis showed that there was a very significant correlations between V and Ca, Fe, Ni and Ba (P<0.01). The results of principal component analysis showed that the score of Astragalus in October ranked first. The orthogonal projections to latent structures discriminant analysis showed that Zn, Ni, Cu and V were the main characteristic elements for identifying Astragalus membranaceus in different growth stages. Conclusion: The content of inorganic elements in Astragalus membranaceus was closely related to its growing stage and inorganic elements could be used as one of the indexes to determine the harvest period of Astragalus membranaceus. Comprehensive analysis showed that middle October was the best harvest time for Astragalus membranaceus.